О гладкости обобщенных решений третьей краевой задачи для эллиптического дифференциально-разностного уравнения - Цветков, Е.Л. (Український математичний журнал, 1993)
Unlike the case of elliptic differential equations, the generalized solutions of elliptic difference-differential may appear to be nonsmooth in the domain Q remaining smooth only on certain subdomaines Qr⊂Q. Conditions for the generalized solutions of the third boundary value problem to remain smooth on the boundary of the neighboring subdomaines Qr are considered.